A million views - Starmer, Aaron, 1976- (Penguin Workshop, 2022)
Brewster Gaines loves making videos to post on YouTube, and his one goal in life is to make a video that gets a million views. He asks charismatic new kid Carly to star in a ten-second video, but things soon get out of hand when Carly's intimidating friend Rosa joins them. Brewster soon finds himself joining forces with four other young artists to produce a trailer for an epic fantasy film. As the kids try to finish the trailer on time, Brewster learns some important lessons about friendship, family, and going viral.